Pembangunan Hukum Perkawinan Indonesia di Era Globalisasi - Khoirul Anwar (UIN Sunan Kalijaga Yogyakarta, 2014)
Not only in the field of general law, family law Indonesia received extensiveinfluence with the era of globalization. Indonesia through Law No. 7 of 1984 hasratified the international convention on the elimination of all forms of discriminatorytreatment of women, known as CEDAW (The convension on the Elimination of AllForms of Discrimination Against Women). Logical consequence of ratification of thisconvention, Indonesia is obliged to implement all the provisions of the Convention. Inthis case the point of tangency with a very strong family law. Supposedly the developmentof the law including family law and more specifically, is the law of marriage, rooted andis looking complexion pure personality of the Indonesian nation has a philosophy ofPancasila and still show the universality in the presence of other nations. But in fact theswift global legal effect outside the substance deviate from the value of living in selfnation, it is felt as described in this paper. Therefore, this paper wants to examine theinfluence of globalization on marriage law in Indonesia, and how should the attitude ofthe Indonesian nation in the face of the effects of globalization on the law of marriage.